The gene expression and enzymatic activity of pinoresinol-lariciresinol reductase during wood formation in Taiwania cryptomerioides Hayata - Chiang, Nien-Ting; Ma, Li-Ting; Lee, Yi-Ru; Tsao, Nai-Wen; Yang, Chih-Kai; Wang, Sheng-Yang; Chu, Fang-Hua (Holzforschung, 2019)
Taiwania ( Hayata) is an indigenous conifer species of Taiwan. Various secondary metabolites of Taiwania with diverse bioactivities have been identified, and lignans are especially abundant in the heartwood (hW). In the present study, the wood of this species was separated to cambium (Cam), sapwood (sW), transition zone (TZ) and hW and their transcriptomes were sequenced. Three pinoresinol-lariciresinol reductases ( s; designated , and ), which are responsible for lignan biosynthesis, were cloned and their expressions in wood tissues were detected. s had higher expression levels in Cam and sW in RNA-seq and reverse transcriptase-polymerase chain reaction (RT-PCR) results. Liquid chromatography-mass spectrometry (LC-MS) analysis of the reaction products of TcPLRs revealed that TcPLR1 can reduce (+)-pinoresinol to lariciresinol, and both TcPLR2.2 and TcPLR3 could reduce (+)-pinoresinol to lariciresinol and secoisolariciresinol.